Representatividades e auto-representação no ensino de Arte - Malheiros, Jorge Aladir da Cruz (2021)
This research discusses the use of artistic productions together with proposals for representation and self-representation in the teaching of Art, seeking to insert themes of diversity in the teaching of visual arts, pluralizing the students' image / aesthetic universe and to assist in the historical repair of cultural invisibilities in Art History. The initial proposal of this study goes through experiences and observations that I witnessed as a teacher of Basic Education, a place where the aesthetic deficiencies and the invisibilities of different cultures remain distant. Reflecting on the black representativeness for the teaching of Art, when looking at Kehinde Wiley's work in an educational practice, I aimed not only at mentioning him as a simple example, but to work so that students could see themselves, identify themselves and produce knowledge in an associated way to make arts education more inclusive and rich, breaking cultural invisibilities and honoring the image of the society around us. Thus, we realize how the work of an Afro-descendant artist can contribute to Afrodescendant representativeness and other markers and subjectivities in arts education, as well as in the way we relate to visual culture.